Predictors of subjective and physiological craving during VR-cue exposure in alcohol use disorder: an explorative single-arm clinical study - Alva Lütt; Nadja Ruckser; Alessandro Turno; Nikolaos Tsamitros; Jil Zoé Fuhrmann; Daniel Schulze; Philipp Stepnicka; Daa Un Moon; Felix Bermpohl; Malek Bajbouj; Robert Schöneck; Miriam Sebold; et al. (BMC Psychiatry, 2026)
Abstract Background Craving is a diagnostic criterion and predictive factor in alcohol use disorder (AUD). In Virtual Reality Cue Exposure (VR-CE), it is intentionally induced as a basis for Virtual Reality Cue Exposure Therapy. As the underlying subjective and physiological factors and predictors of craving are still incompletely understood, we aim to identify factors associated with craving responses during VR-CE in patients with AUD. Methods Craving responses of 61 patients with AUD during VR-CE were measured using subjective ratings (visual analogue scale, VAS) and physiological parameters, including electrodermal activity (EDA, non-specific skin conductance responses (NS.SCR) and skin conductance level (SCL)), heart rate (HR), heart rate variability (HRV), brightness corrected pupil diameter (BCPD) and respiration rate (RR). To determine factors associated with craving responses, VR-related characteristics, patients’ AUD characteristics and patients’ pre-VR craving characteristics were analyzed using linear mixed-effects models. Results The VR-related characteristic drink choice ( p = .038), several AUD-characteristics ( AUDIT score : p = .019; ADS score : p < .001; amount of alcohol consumed in the past five years : p = .031) and pre-VR craving characteristics ( AUQ score : p < .001; OCDS score : p < .001) significantly influenced subjective craving during VR-CE. The VR-related characteristic type of risk scenario ( p = .005) influenced the HRV parameter Very Low Frequency Band (VLFB). Several AUD-characteristics ( AUDIT score : p = .007; ADS score , p = .003; days since last alcohol consumption : p = .018) and the pre-VR OCDS score ( p = .015) were associated with changes in RR. Conclusions Clinical characteristics, particularly AUD severity and pre-VR craving were more consistently associated with craving responses than VR-specific factors. The limited overlap between subjective and physiological measures highlights the complexity of the concept craving and underlines the importance of using multidimensional assessments. This study contributes to a better understanding of predictors on craving and may inform the further development of optimized VR-based interventions for AUD. Trial registration This study followed a pre-published study protocol and was preregistered on ClinicalTrials.gov (NCT05861843, Registration Date: 2023-04-24).